Increased CSF Soluble TREM2 Concentration in Patients With Neurosyphilis - Li, Wurong; Chang, Haoxiao; Wu, Wenqing; Xu, Dongmei; Jiang, Meijuan; Gao, Junhua; Huang, Yuming; Xu, Yun; Yin, Linlin; Zhang, Xinghu (Frontiers in Neurology, 2020)
ABSTRACT Objective: To explore cerebrospinal fluid (CSF) levels of soluble triggering receptor expressed on myeloid cells 2 (sTREM2) and neurofilament light proteins (NFL) in patients with neurosyphilis (NS). Methods: We enrolled 71 NS patients (41 early-NS and 30 late-NS patients) and 20 syphilis but non-NS patients whose CSF samples were collected. The CSF levels of the microglial activation biomarker sTREM2 and neuronal injury biomarker NFL were measured using ELISA. Results: CSF sTREM2 levels were significantly higher in NS patients compared to those in syphilis/non-NS patients (p < 0.001). In a subgroup analysis, the CSF sTREM2 levels elevated significantly in late-NS patients than those in early-NS patients (p < 0.001). The CSF sTREM2 levels in early-NS group were also significantly higher than those in syphilis/non-NS group (p = 0.024). Like CSF sTREM2, similar differences between groups were also found in CSF NFL. There was a moderate correlation between CSF sTREM2 and CSF NFL (r = 0.406, p < 0.001) in NS group. Conclusions: CSF sTREM2 levels elevated in NS and peaked at the late stage, suggesting that CSF sTREM2 may be a useful marker to quantify microglia activation in NS and play a role in the progression of NS. The positive correlation between CSF sTREM2 and CSF NFL indicates a linkage between microglial activation and neuronal injury in NS.